Política pública, justicias y necesidades. Aproximaciones desde el abordaje del embarazo a edades tempranas - Bermúdez, Mónica Solange De Martino (Universidad Santiago de Cali, 2020)
This chapter deals with public policy as an organized response of the sta-te in relation to needs felt by the population, based on an ethical sense of political action, understood as the joint activity of those who feel such needs. We understand that public policy is placed as a limit horizon in the analysis, which does not allow to deepen the quality of justice and legal assets to defend. Therefore, this article demands an analysis and reflec-tion, by the care professions, that goes beyond the limits of a specific po-licy or program accessing the needs felt by those affected and their forms of socio-political organization, of such in this way justice would appear as a new reflective horizon that until now is not presented clearly. For these reflections we use research Visiting Teen Paternity in Contexts of Poverty, funded by the Sectorial Commission of Scientific Research of the Univer-sity of the Republic, especially interviews conducted with technicians who work around pregnancy at an early age.